Карпатські полонини і полонинське господарство - Малиновський, К. (Праці наукового товариства ім. Шевченка, 2003)
Повідомлено про сучасний стан карпатських полонин, найпоширеніші на
полонинах типи рослинности, їхнє походження, продуктивність і кормову цінність. Наголошено на вторинному походженні фітоценозів і заходах, спрямованих на організацію пасовищного господарства. The modern vegetation of the Carpathian mountain valleys is in general introduced by
secondary communities formed in place of elfin wood consisting of Pinus mugo and Alnus
viridis, Rhododendronetum, communities of high grass and mountain forests situated on the
upper line of growth. Primary communities are preserved in places, inapproachable to
pastures. The greatest space among secondary communities occupy uniform and low
productive communities of Nardetum strictae, Myrtilletum, Festucetum rubrae. Degraded
Juncetum trifidi, Caricetum sempervirensis, Festucetum supinae are widespread in the
Alpine chord. For the purpose to ameliorate pastures the author recommends to introduce
paddock system of pastures, deposit organic fertilizers and seed productive aft grass.